2009
DOI: 10.1002/9780471729259.mc16a01s14
|View full text |Cite
|
Sign up to set email alerts
|

Growth Conditions for Plant Virus–Host Studies

Abstract: Plant virus replication and spread require specific interactions between the obligate organism, the virus, and its host, the plant. Both virus and plant factors, whether they are involved in virus accumulation or in defense against virus accumulation, require specific environmental conditions to maximize their activity. In order to understand how virus and plant factors function, it is therefore necessary to understand and control the environment that influences their activity. Temperature, light, moisture, ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…This showed that the symptoms that appear on plants infected by specific isolates can be visually different. Plant and environmental conditions also influence disease symptoms due to pathogen infestation (Liu et al, 2009). Both isolates caused changes in the leaves of melon and bitter melon plants, namely the blanching of the lamina and the formation of striped patterns on the plant leaves.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that the symptoms that appear on plants infected by specific isolates can be visually different. Plant and environmental conditions also influence disease symptoms due to pathogen infestation (Liu et al, 2009). Both isolates caused changes in the leaves of melon and bitter melon plants, namely the blanching of the lamina and the formation of striped patterns on the plant leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Drought has also been shown to negatively affect virus translocation in plants (Liu et al 2009). For example, drought inhibits the systemic spread of tomato spotted wilt virus in tomato (Cordoba et al 1991).…”
Section: Plant-viral Interaction During Drought Stressmentioning
confidence: 98%
“…Plant viral infections are influenced by a variety of environmental factors (Kassanis 1957;Liu et al 2009). However, many questions remain regarding the relationship between temperature, virus propagation, and host-responses (Honjo et al 2020).…”
mentioning
confidence: 99%